Real and metaphorical hunger: the case of The Divergent Trilogy (Altre Modernità, 2015)
The present contribution investigates how the issue of hunger becomes a means of expressing and communicating personal and social identity in Veronica Roth’s best seller trilogy Divergent (2011-13). Roth portrays a dystopian future developing a multifaceted concept of hunger, both real and figurative, and using food as a cultural metaphor. The trilogy is set in a post-apocalyptic Chicago, whose population is divided into five allegorical factions, according to a number of personal and social characteristics. The life of each faction seems to be based on a form of metaphorical hunger: those who pursue selflessness and altruism belong to Abnegation, peace and harmony to Amity, honesty and truth to Candor, danger and adventure to Dauntless, and knowledge and power to Erudite. Those people who are excluded become factionless: they are outcasts who live their life in extreme poverty and experience real physical hunger. On the other hand, I will show how the numerous references to food and eating pervading the novels help to map the characters’ personalities and identities as single individuals and as groups.